2014
DOI: 10.1080/13811118.2013.824838
|View full text |Cite
|
Sign up to set email alerts
|

Examining Non-Suicidal Self-Injury among Adolescents with Mental Health Needs, in Ontario, Canada

Abstract: The objectives of this study were to examine the prevalence of non-suicidal self-injury (NSSI) among adolescents with mental health needs and specific factors associated with NSSI among adolescents aged 14 to 18 years who received mental health services in adult mental health facilities in Ontario, Canada. Data on 2,013 adolescents were obtained from the Ontario Mental Health Reporting System using the Resident Assessment Instrument-Mental Health (RAI-MH) and were analyzed using logistic regression. Approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 64 publications
3
13
0
1
Order By: Relevance
“…On the basis of previous literature, gender was expected to be an important potential risk factor for adolescent engagement in NSSI, SSI, and substance use. Consistent with previous research, it was found that females were more likely than males to engage in both NSSI and SSI (Hamza et al., ; Miller et al., ; Sornberger et al., ; Stewart, Baiden, & Theall‐Honey, ). Furthermore, elevated levels of depressive symptoms, which were more common among female adolescents as compared to males, were strongly predictive of NSSI and SSI (e.g., Jenkins, Singer, Conner, Calhoun, & Diamond, ).…”
Section: Discussionsupporting
confidence: 86%
“…On the basis of previous literature, gender was expected to be an important potential risk factor for adolescent engagement in NSSI, SSI, and substance use. Consistent with previous research, it was found that females were more likely than males to engage in both NSSI and SSI (Hamza et al., ; Miller et al., ; Sornberger et al., ; Stewart, Baiden, & Theall‐Honey, ). Furthermore, elevated levels of depressive symptoms, which were more common among female adolescents as compared to males, were strongly predictive of NSSI and SSI (e.g., Jenkins, Singer, Conner, Calhoun, & Diamond, ).…”
Section: Discussionsupporting
confidence: 86%
“…Our findings add to the extant literature and underscore the harmful effect of bullying (Finkelhor et al, 2005;Storch and Ledley, 2005). The desire to regulate mood and affect is one consistent reason that has been adduced in explaining adolescent NSSI behavior (Nock, 2010;Noll et al, 2003;Stewart et al, 2014). A qualitative study undertaken by Long et al (2015) shows that many of their participants engaged in NSSI as a means to manage the traumatic life experience and emotional distress.…”
Section: Discussionsupporting
confidence: 57%
“…In a large ( N = 2,980) study carried out by Christoffersen and colleagues in 2015 ( 25 ), individuals with a history of CM, peer victimization at school, or other adverse experiences were six times more likely to report NSSI than participants without this history. Stewart et al ( 26 ) confirmed that sexual abuse was associated with NSSI in a sample of adolescents who accessed mental health services. Finally, in the study of Stinson and colleagues ( 27 ) in a sample of 381 forensic mental health inpatients, traumatic experiences enhanced the likelihood of self-harm and suicide attempts.…”
Section: Resultsmentioning
confidence: 94%